Neutrino masses in SU(5) X U(1)F with adjoint flavons (2012)
ABSTRACT: We present a SU(5) x U(1)F supersymmetric model for neutrino masses and mixings that implements the seesaw mechanism by means of the heavy SU(2) singlets and triplets states contained in three adjoints of SU(5). We discuss how Abelian U(1)F symmetries can naturally yield non-hierarchical light neutrinos even when the heavy states are strongly hierarchical, and how it can also ensure that R{parity arises as an exact accidental symmetry. By assigning two flavons that break U(1)F to the adjoint representation of SU(5) and assuming universality for all the fundamental couplings, the coe cients of the e ective Yukawa and Majorana mass operators become calculable in terms of group theoretical quantities. There is a single free parameter in the model, however, at leading order the structure of the light neutrinos mass matrix is determined in a parameter independent way.